Mailza Assis, a woman on the rise - Rocha , Sandra Maria Amorim da; Benevides, Siomary Cintia dos Santos (Seven Editora, 2023)
This article aims to explain a little about the history of Acre, its political formation and the phenomena that took place during the political consolidation of Mailza Assis. It is argued that Acre is a State whose growth process took place in a migratory manner, and in this situation, political formations, parties and coalitions began and little by little they identified their political leaders and embedded them in society. In this circumstance, Mailza Assis sees an opportunity in the political space to provide changes to Acre society, and begins to redefine its goals, so that its work reaches people, through public policies. In this way, he deepens his participation in political spaces and his journey has been marked by ethics and understanding of the State’s social issues. DOI:https://doi.org/10.56238/interdiinovationscrese-052